Analysis Of Job Satisfaction, Job Stress, And Work Environment On Employee Performance At The Department Of Cooperatives, Smes, Industry And Trade Of Medan City - Agustin, Vini Deva; Malikhah, Ikhah; Istiqamah, Nuraini Kemalasari (Jurnal Fokus Manajemen, 2025)
This study aims to analyze job satisfaction, work stress, non-physical work environment on employee performance at the Cooperatives, SMEs, Industry and Trade Office of Medan City. This study uses an associative and quantitative approach. This study was conducted at the Cooperatives, SMEs, Industry and Trade Office of Medan City. The population in this study were all employees of the Cooperatives, SMEs, Industry and Trade Office of Medan City, totaling 81 employees. This study used saturated sampling, namely 81 employees as samples. The data analysis technique used was multiple linear regression. The results of this study are: In this study, Job Satisfaction partially influences the performance of Employees at the Cooperatives, SMEs, Industry and Trade Service of Medan City, this can be seen from the calculated t value> t table (5.784> 1.990) and the significance level of 0.000 <0.05. In this study, Job Stress partially influences and is significant to the performance of Employees at the Cooperatives, SMEs, Industry and Trade Service of Medan City, this can be seen from the calculated t value <t table (2.879> 1.990) and the significance level of 0.005 <0.05. In this study, the Work Environment partially influences the performance of Employees at the Cooperatives, SMEs, Industry and Trade Service of Medan City. This can be seen from the calculated t value> t table (6.736> 1.990) and the significance level of 0.000 <0.05. The independent variables consisting of Job Satisfaction (X_1), Job Stress (X_2), and Work Environment (X_3) simultaneously have a significant effect on the performance of Employees at the Cooperatives, SMEs, Industry and Trade Service of Medan City.